Pembelajaran Pelafalan Bahasa Inggris melalui Teknik Sulih Suara - Suwartono Suwartono (LPMPP Universitas Negeri Yogyakarta, 2006)
Pronunciation is an essential part in language, for the nature of language is spken. But, most learners of Engglish in the environment where a research was undertaken faced problems with the pronunciation of English. Ths study aims (1) finding out the effectiveness of dubbing aas technique for teaching the pronunciation of English, and (2) identifying the commonly mispronounced sounds of English.The experimental study involved semester 1 students of English Department of Teachir Training and Education Faculty of Universita Muhammadiyah Purwokerto in the Academic Year 2005/2006. Out of 120 student that had been split into 5 smaller groups by the management authority for practical purpose, 2 grups have been chose as the research sample groups on the basis of equality in the pre-test result. Group A2 has been the Expreimental Group and Group A1 has been the Congrol Group. The teaching dan learning process in te former employed dubbing system as the main technique, while the classroom learning activities is the latter used drill in most of the time. After 6 sessions (within 6 weeks) a post-test was administered. Data collected through the post-test were analyzed using descriptive statistical opeerations of mean, frequency distribution, percentage and the t-test inferential statistical tool